2010
DOI: 10.2478/v10078-010-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota Leisure Time Physical Activity Questionnaire as an additional Tool in Clinical Assessment of Patients undergoing Percutaneous Coronary Interventions

Abstract: Minnesota Leisure Time Physical Activity Questionnaire as an additional Tool in Clinical Assessment of Patients undergoing Percutaneous Coronary Interventions The aim was to analyze the usability of Minnesota Leisure Time Physical Activity Questionnaire (MLTPAQ) in assessment of physical activity in patients before and 6 months after percutaneous coronary intervention (PCI). The study group consisted of 211 patients aged between 34-79 years (x = 59,5±7,89 yeras), with history of ischemic heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…Patients who trained with a suspension system, as well as those following a standard program, achieved a significant improvement, i.e., the duration of their final test was longer by about 2 min ( p < 0.000) and the distance covered was greater by more than 100 m ( p < 0.000). The obtained results are in line with the results of other authors [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients who trained with a suspension system, as well as those following a standard program, achieved a significant improvement, i.e., the duration of their final test was longer by about 2 min ( p < 0.000) and the distance covered was greater by more than 100 m ( p < 0.000). The obtained results are in line with the results of other authors [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is affected by reduced activity of the autonomic nervous system. This mechanism, as well as the excitation of the vagus nerve, also lead to a decrease in both systolic and diastolic pressure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher physical activity among younger patients after LTx was also reported [ 24 ]. Returning to work after LTx was not related to the level of physical activity in leisure time, perhaps due to a lack of time for systematic physical activity.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, authors concluded that exercise training in patients with ventricular dysfunction may have beneficial effects on cardiac function, at the same time without adversely affecting the reconstruction of the left ventricle and causing no serious cardiac complications [23]. Similar results obtained Nowak et al (2010) who after the 6-month follow-up reported a significant increase in the LVEF (51,64 vs 52,45%, p<0,02) and no significant changes in the LVEDD (51,10 vs 51,35 mm) and LVESD (34,93 vs 34,33 mm) indicators [24]. The direction of changes observed by these authors is consistent with our results in which LVEDD and LVESD parameters were not significantly different after 22 training units in the Indoor Cycling and standard group and the LVEF value of these groups was an irrelevant, but still an increase of more than 1%.…”
Section: Discussionmentioning
confidence: 56%
“…Our analysis showed a slight increase in LVM and LVMI in both cardiac comprehensive rehabilitation groups. Noteworthy is fact that in the Indoor Cycling and standard group average value of LVMI was lower than 116 kg/m 2 classified as a moderate left ventricular hypertrophy [26] [24]. The overall conclusion is that the effect of exercise training on myocardium has not been clearly explained yet.…”
Section: Discussionmentioning
confidence: 99%